THE NEED FOR POLICE ACTION CONTROL - Matisāns, Juris (Administrative and Criminal Justice, 2016)
Police authorities within the competence fulfils an important role ensuring public interest in the resolution of different types of situations and conflicts. Ways police is controlled is considered to be an issue. Unlimited discretion of authorities is not allowed, but independence would be considered one of the prerequisites for the effective operation of the authority. Aim of this article is to draw attention to certain factors that illustrate different approaches to police control over the time.